Hubungan Menonton Sinetron Percintaan Dan Membaca Cerita Percintaan Dengan Perilaku Seks Remaja - Amin,M.Psi, Drs.Abdul (HERITAGE, 2014)
This research conducted to know how much influence the intentions of drama andstorybooks about romance to adolescent sexual behaviors. The sampling technique usedpurpossive sampling. Data collected used free sex scale, scale of the intentions readingromance stories, and scale of the intentions watching romance drama. The calculation isdone by using SPSS 2000, from 60 items free sex scale obtained 59 valid items and 1 fallitem with correlation coefficient between 0,230 to 0,908 and coefficient of reliability between0,885 to 0,938. From 40 items scale of the intentions reading romance stories obtained 36valid items and 4 fall items with correlation coefficient between 0,265 to 0,715 and coefficientof reliability between 0,691 to 0,844. From 35 scale of the intentions watching romancedrama obtained 34 valid items and 1 fall item with correlation coefficient between 0,298 to0,694 and coefficient of reliability between 0,556 to 0,780.Data analysis techniques using variance analysis and regression analysis. This resultproof that there are relationship between reading romance stories and watching romancedrama to free sex, where Freg = 2.533 with p = 0.041 ( p â‰¤0.050 ) that mean is significant.This result proof that any difference about free sex adolescent between boys and girls,where F = 21.008, db = 1 dan p = 0.000 (p â‰¤0.010).